Pengaruh Sukuk, Inflasi, Suku Bunga, Dan Pertumbuhan Ekonomi Terhadap Simpanan Dana Ketiga Perbankan Syariah - Catur Aldiansyah; Tri Inda Fadhila Rahma (UNIVED Press, 2023)
Third party funds (DPK) are usually known as community funds which are funds collected by banks originating from the public in a broad sense, including individual communities, as well as bank business entities that offer deposit products to the public in raising funds. Third party funds are the main component in Islamic bank capital because third party funds are an important variable which is the main source of bank funds. The existence of third party funds is influenced by various factors in the collection of public funds. These factors cannot be separated from the existence of Sukuk, Inflation, Interest Rates, and Economic Growth. This study aims to examine the effect of Sukuk, Inflation, Interest Rates, and Economic Growth on third party funds in Indonesian Islamic Banking for the 2009-2021 Period. Time series data published by Bank Indonesia (BI), Indonesian Financial Authority (OJK), Central Bureau of Statistics (BPS) are used in this study. Testing was carried out using empirical methods using a path analysis model to support the research hypothesis. The results showed that the rate of sukuk had a positive effect of 10.81%, Inflation had a positive effect of 19.06%, interest rates had a positive effect of 24.22%, and economic growth had a positive effect of 18.27%. These results indicate that all the factors studied have an influence and are significant on Islamic banking third party funds.